Pelvic Fracture Urethral Injury in Females - Pankaj M. Joshi; Marco Bandini; Christian Yepes; Shreyas Bhadranavar; Vipin Sharma; Sandeep Bafna; Sanjay B. Kulkarni (Société Internationale d’Urologie Journal)
BackgroundPelvic fracture urethral injuries (PFUI) in females are very rare. The available literature on the management of this condition is scarce and not clear, mainly because of limited experience among reconstructive surgeons. We present our experience of management of these complex urethral injuries in female patients.Materials and MethodsWe collected data, retrospectively and prospectively for 22 female patients referredto our center for PFUI repair between 1995 and 2021. During the clinical assessment of these complex injuries, following our internal institutional protocol, all patients underwent pelvic MRI (bladder and urethra are filled with saline solution and jelly to enhance the urethral lumen and the level of the distraction) before anastomotic urethroplasty. ResultsPFUI compromised the mid urethra in 10 patients (45.5%). A transabdominal approach was used in 8 patients (80%), and urethra-vaginal fistula repair was undertaken in 6 patients (60%). After a median follow-up of 36 months, only 1 patient with proximal PFUI required a surgical revision without compromising urinary continence. ConclusionsThe most common site of urethral involvement in pelvic fracture is mid urethral, which is owing to avulsion. Urethra-vaginal fistula should be suspected. Treatment consists in anastomotic urethroplasty, mainly through the abdominal approach.